Durabilite De L’aquaculture Dans La Zone Rurale De La Lagune Ébrie En Cote D’ivoire: Mise En Question - Aboya Narcisse; Kouadio Nanan Kouame Felix; Koudou Dogbo (European Scientific Journal, ESJ, 2016)
The space Ébrié lagoon borders the cities of Abidjan, Bingerville, Dabou and Jacqueville. Little influenced by the sea, the lagoon is a suitable area for livestock breeding fish. The scarcity of the resource has led the residents to be converting in aquaculture. It is a extensive aquaculture are of modern practices and so-called traditional family. Despite the willingness of the few actors of this rural area, this activity is under the pressure from unfavorable natural factors, restrictions imposed by Ébrié villagers to occupy a portion of the lagoon and the pollution of anthropogenic activities. The development of aquaculture is under the influence of the dredge lagoon funds and numerous solid waste produced by man. The study used bathymetric maps to locate and identify the areas and depths of aquaculture farms. Forms of degradation, water pollution have been obtained by field observations and photographs, while the surface operated by the dredge was measured with a measuring tape values were determined using the formula mathematics for calculating the area of a geometric figure (circle, rectangle, etc.). The effects of natural factors and human activities have been examined by administering a questionnaire to approximately fifty actors chosen at random. Focus group discussions were held between men and women in order to supplement the information obtained from the survey questionnaire. The study showed that only sectors Bingerville and Jacqueville practicing aquaculture. The size of the fish farms is based on the financial capacity of the owner. This activity demonstrates the introduction of an integrated management of the lagoon for sustainable aquaculture.